Insights into post-transcriptional regulation during legume-rhizobia symbiosis - Reynoso, Mauricio Alberto (2012)
During the past ten years, changes in the transcriptome have been assessed at different stages of the legume-rhizobia association by the use of DNA microarrays and, more recently, by RNA sequencing technologies. These studies allowed the identification of hundred or thousand of genes whose steadystate mRNA levels increase or decrease upon bacterial infection or in nodules as compared with uninfected roots.1-7 However, transcriptome based-approaches do not distinguish between mRNAs that are being actively translated, stored as messenger ribonucleoproteins (mRNPs) or targeted for degradation. Despite that the increase in steady-state levels of an mRNA does not necessarily correlate with an increase in abundance or activity of the encoded protein, this information has been commonly used to select genes that are candidates to play a role during nodule organogenesis or bacterial infection. Such criterion does not take into account the post-transcriptional mechanisms that contribute to the regulation of gene expression. One of such mechanisms, which has significant impact on gene expression, is the selective recruitment of mRNAs to the translational machinery. Here, we review the post-transcriptional mechanisms that contribute to the regulation of gene expression in the context of the ecological and agronomical important symbiotic interaction established between roots of legumes and the nitrogen fixing bacteria collectively known as rhizobia.8 In addition, we discuss how the development of new technologies that allow the assessment of these regulatory layers would help to understand the genetic network governing legume rhizobia symbiosis.